METODE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP MOTIVASI READING COMPREHENSION MAHASISWA DI UNIVERSITAS TEKNOLOGI MATARAM - Pathul Indriana; Syawal Syawal (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This research is entitled Cooperative Integrated Reading and Composition (CIRC) Method on Students' Reading Comprehension Motivation at Mataram University of Technology. The purpose of this study was to overcome the low reading comprehension motivation of the second semester students of the Informatics Engineering study program at the Mataram University of Technology. This study used an experimental method design as a research design. This is the simplest design that examines two treatments, where each treatment is varied into two treatment levels. The experimental group consisting of 22 students was given treatment using the CIRC method, while the control group used conventional methods in the teaching and learning process. In applying the CIRC method to the experimental group, the researcher divided students into small groups consisting of 4 to 5 people per group, then students carried out the stages of implementing the CIRC method. Data collection was obtained based on the results of the pre-test, post-test, results of filling out questionnaires and observations during the learning activities. The data were processed using SPSS and the results were analyzed using a descriptive statistical model where the research data were presented and described based on data obtained from observations, questionnaires, interviews, pre-test and post-test results, and conclusions were obtained regarding the success rate of applying the CIRC method. The results showed that the average score of students in the post-test showed greater results when compared to the achievement scores in the pre-test, namely (79.50> 62.01. The conclusion that can be drawn from this study is that the CIRC method is effectively applied to students' Reading Comprehension learning in English courses and the application of the CIRC method to the learning process can increase student learning motivation.